To explore the risk factors and preventive measures affecting the treatment of retrosternal goiter: An observational study. Issue 44 (30th October 2020) - Li, Wei; Li, Huisheng; Zhang, Shanling; Tao, Yingjie; Wang, Xudong; Cheng, Junping
Abstract : Abstract: The definition of substernal goiter (SG) is based on variable criteria, leading to considerable variations in the reported incidence (from 0.2% to 45%). The peri- and postoperative complications are higher in total thyroidectomy (TT) for SG than that for cervical goiter. This study aimed to evaluate the preoperative risk factors associated with postoperative complications. From 2002 to 2014, 142 (8.5%; 98 women and 44 men) of the 1690 patients who underwent TT had a SG. We retrospectively evaluated the following parameters: sex, age, histology, pre- and retro-vascular position, recurrence, and extension beyond the carina. These parameters were then related to the postoperative complications: seroma/hematoma, transient and permanent hypocalcemia, transient and permanent laryngeal nerve palsy, and the length of surgery. The results were further compared with a control group of 120 patients operated on in the same period with TT for cervical goiter (CG). Statistical analysis (Student t test and Fisher exact test) indicated an association between recurrence and extension beyond the carina with all postoperative complications. The group that underwent TT of SG showed a statistically significant higher risk for transient hypocalcemia (relative risk = 1.767 with 95% confidence interval: 1.131–2.7605, P = .0124, and need to treat = 7.1) and a trend toward significance for transient recurrent laryngeal nerve palsy (relative risk = 6.7806 with 95% confidence interval: 0.8577–53.2898, P = .0696, and need to treat = 20.8) compared with the group that underwent TT of cervical goiter. The major risk factors associated with postoperative complications are recurrence and extension beyond the carina. TT is the procedure to perform in SG even if the incidence of complications is higher than cervical goiters. The major risk factors associated with postoperative complications are recurrence and extension beyond the carina.